2009
DOI: 10.2337/dc08-1710
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Is a Strong Predictor of Cardiovascular Events in Elderly Men With the Metabolic Syndrome

Abstract: OBJECTIVE -The aim of this study was to investigate the role of inflammatory markers as potential predictors of cardiovascular events in subjects with and without the metabolic syndrome.RESEARCH DESIGN AND METHODS -This was a post hoc analysis from the Diet and Omega-3 Intervention Trial (DOIT), comprising 563 elderly men with (n ϭ 221) and without (n ϭ 342) metabolic syndrome. Circulating inflammatory markers were measured.RESULTS -During 3 years, 68 cardiovascular events were recorded. In the total populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 26 publications
10
57
0
Order By: Relevance
“…Overall, these results illustrate that increased circulating concentrations of proand anti-inflammatory cytokines are generally affected by BMI and other potential confounders. This observation did not hold true for IL-10, which was detected in 44% of individuals only, similar to the findings in previous studies [42][43][44][45]. Differences in cytokine concentrations between those with type 2 diabetes and those with both autoimmune diabetes types are not solely explained and influenced by these potential confounders, suggesting a diabetes-type associated immune dysregulation.…”
Section: Discussionsupporting
confidence: 77%
“…Overall, these results illustrate that increased circulating concentrations of proand anti-inflammatory cytokines are generally affected by BMI and other potential confounders. This observation did not hold true for IL-10, which was detected in 44% of individuals only, similar to the findings in previous studies [42][43][44][45]. Differences in cytokine concentrations between those with type 2 diabetes and those with both autoimmune diabetes types are not solely explained and influenced by these potential confounders, suggesting a diabetes-type associated immune dysregulation.…”
Section: Discussionsupporting
confidence: 77%
“…Whereas IL-6 and PAI-1 are thought to at least be partially derived from adipose tissue, not much is known on the source of IL-18 [12]. It has previously been suggested that non-fat cells are the main source of IL-18 in adipose tissue, whereas a recent study found an enhancing eff ect of intermittent high glucose on IL-18 expression in cultured adipocytes [5,13]. However, the exact cellular source remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A pro-infl ammatory eff ect of altered glucose metabolism is discussed [5]. Most clinical studies have focused on hyperinsulinaemia and insulin resistance, whereas most pre-clinical studies have investigated direct eff ects of insulin and advanced glycosylated endproducts (AGE) [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Elevated serum levels of IL-12 and IL-18 have also been observed in several human disease states including metabolic syndrome, obesity, type 2 diabetes, hypertension, and systemic lupus erythematosus (SLE). [4][5][6][7] Noninvasive measurements of arterial stiffness, including aortic pulse wave velocity (PWV) and augmentation index (AIx), are established surrogate markers of CVD-associated and all-cause mortality in the general population, and may have utility in CVD-risk stratification. 8 IL-18 is independently associated with CVD-related outcomes and also PWV in prospective and cross-sectional studies limited to individuals with CVD risk factors.…”
Section: Doi:101093/ajh/hps032mentioning
confidence: 99%